The Effect of Combination of Nutrition on Growth and Yield of Water Spinach Plants in NFT Hydroponic System - Darwin Pangaribuan; Kirana Ceri Fortuna; Sri Ramadiana; RA. Diana Widyastuti (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2025)
A hydroponic system is a technique for growing plants without soil, utilizing water combined with nutrients as a replacement for soil. The purpose of this research was to determine the most effective combination of treatments between AB – Mix with liquid organic fertilizer (LOF) shrimp waste extract, LOF chicken manure extract, and eco-enzyme solution in supporting the growth of water spinach plants in the NFT hydroponic system. This research applied a Randomized Block Design with four types of treatments: AB – Mix 100% as a control, AB – Mix 75% + 15% shrimp waste extract + 10% chicken manure extract + 0 ml/l eco enzyme solution, AB – Mix 75% + 15% shrimp waste extract + 10% chicken manure extract + 1 ml/l eco enzyme solution, AB – Mix 75% + 15% shrimp waste extract + 10% chicken manure extract + 2 ml/l eco enzyme solution.. The results showed that the combination of AB-Mix with shrimp waste extract, chicken manure extract, and eco-enzyme produced the best results for hydroponic water spinach plants. This study showed the potential of using organic waste as an alternative nutrient from the treatment of AB-Mix 75% + 15% shrimp waste extract + 10% chicken manure extract + 0 ml/l eco-enzyme solution, AB-Mix 75% + 15% shrimp waste extract + 10% chicken manure extract + 1 ml/l eco-enzyme solution, and AB-Mix 75% + 15% shrimp waste extract + 10% chicken manure extract + 2 ml/l eco-enzyme solution gave the best results for hydroponic water spinach plants. This study shows the potential for using organic waste as an alternative source of nutrients. Keywords: chicken manure, eco-enzyme, hydroponic NFT, shrimp waste, water spinach